Fracture evaluation of multi-layered precast reinforced geopolymer-concrete composite beams by incorporating acoustic emission into mechanical analysis - Ranjbar, N.; Behnia, A.; Chai, H.K.; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin (Elsevier, 2016)
In this study, a multi-layered steel reinforced composite beams which are composed of geopolymer concrete section at tensile zone and Portland cement based concrete at compression are investigated. The beams were tested to failure to compare the toughness, post peak behaviour and failure mode based on the variation of the depth of layers. The mechanical analysis incorporated into acoustic emission technique showed that the geopolymer beam endured more deflection than the ordinary Portland cement based beams, however their ultimate load carrying capacities were quite similar. Further, the composite beams, resulted in transition of failure mode of shear to a flexural.